TINGKAT PENGETAHUAN MAHASISWA TEKNIK MESIN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA MENGENAI NOISE INDUCED HEARING LOSS PADA PRAKTIK MESIN BUBUT - NANDA ALIFIA RIZKI HAFIZAH; IRFAN HAMDANI (LP2MTBM MAKARIOZ, 2021)
Worldwide, 16% of hearing loss that occurs in adults is caused by noise arising from the work environment. The NationalInstitute of Health reports that 15% of Americans aged 20-69 experience hearing loss due to work activities. The results ofresearch conducted in the city of Medan showed 53.6% of workers experiencing hearing loss in workers who work in noisyenvironments. To determine the level of knowledge of UMSU mechanical engineering students about NIHL and compliancewith the use of protective equipment in the practice of lathes. This study used a descriptive method with cross sectionaldesign with a questionnaire instrument and used a total sampling of all UMSU mechanical engineering students in 2016.This study showed that the level of knowledge of UMSU mechanical engineering students regarding NIHL of wellknowledgeedstudents was 87.5 %, well-knowledgeed 6.66% and poorly-knowledgeed 5.83%. The level of knowledge ofUMSU mechanical engineering students regarding compliance with the use of PPE with good knowledge was 90.8%,knowledgeable was good enough as much as 7.5% and those with less good knowledge were 1.6%. It can be concludedthat most UMSU mechanical engineering students have good knowledge of NIHL and compliance with the use of PPE inlathe practice.